Desa Layak Air Bersih dan Sanitasi di Desa Labuhan Rasoki - Indra Hadinata Rambe; Husniah Ramadhani Pulungan (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2022)
Clean water and sanitation are very important needs. This is because without clean water and sanitation on earth cannot take place. Humans, animals, and all plants need clean water and sanitation for their lives. The clean water and sanitation needed by humans must meet both quality and quantity requirements. To get clean water and sanitation that meets the requirements. The community of Labuan Rasoki Village is one of the villages that received assistance from the clean water and proper sanitation program from the government. The purpose of this study was to determine the attitude of public awareness about the importance of maintaining clean water and proper sanitation in Labuan Rasoki Village, East Angkola District, South Tapanuli Regency. This research is qualitative and descriptive in nature to find out will maintain awareness of maintaining clean water and proper sanitation in Labuan Rasoki Village, East Angkola District, South Tapanuli Regency. In obtaining data, the author made direct observations by conducting interviews. From the results of a survey conducted by the author on the lack of awareness, knowledge, attitudes, and actions of the community about clean water and proper sanitation.